Single-cell measurements of two-dimensional binding affinity across cell contacts - Chouliara, M; Junghans, V; Dam, T; Santos, AM; Davis, SJ; Jönsson, P (Cell Press, 2021)
The two-dimensional (2D) affinity between protein molecules across contacting cells is a key parameter regulating and initiating several cellular processes. However, measuring 2D affinity can be challenging and experimental data are limited. In addition, the obtained 2D affinities are typically averaged over the cell population. We here present a method to measure 2D affinity on single cells binding to polyhistidine-tagged fluorescent ligands anchored to a supported lipid bilayer (SLB). By decreasing the density of ligands in the SLB using imidazole a new steady-state accumulation in the contact is obtained, and from this change, both the 2D affinity and the number of receptors on the cell can be determined. The method was validated on an SLB containing rat CD2 binding to the rat CD48 mutant T92A expressed on Jurkat T cells. The addition of imidazole did not influence the average 2D affinity (1/Kd), and the spread in affinities within the cell population was low, Kd = 4.9 ± 0.9 molecules/μm2 (mean ± SD), despite an order of magnitude spread in ligand accumulation due to differences in receptor density. It was also found that cell contact size increased both with ligand density and with the number of receptors per cell, but that the contact size stayed approximately constant when lowering the ligand density, above a density of around 10 rCD2 molecules/μm2, after the contact first had formed, indicative of a heterogeneous process. In summary, this method not only allows for single-cell affinities to be measured, but it can also reduce measurement and analysis time and improve measurement accuracy. Due to the low spread in 2D Kd within the cell population, the analysis can further be restricted to the cells showing the strongest binding, paving the way for using this method to study weak binding events.